2013
DOI: 10.7550/rmb.33904
|View full text |Cite
|
Sign up to set email alerts
|

Tama-risk? Avian responses to the invasion of saltcedars (Tamarix ramosissima) in Sonora, Mexico

Abstract: Although exotic plant invasions are one of the most important components of global change, previous studies have found some of the alien species to provide resources and/or conditions to native biota. One example of this is the saltcedar (Tamarix ramosissima). This exotic invasive tree has been related to several dramatic environmental changes in North America. However, previous studies suggest that they offer resources and conditions for native biota, such as the threatened southwestern willow flycatcher (Emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Malo et al (2012) found that an invasive shrub bolstered abundance of wood mice (Apodemus sylvaticus) by reducing predation risk from avian predators. Similar patterns with respect to invasive plants have been observed in the avian literature when entire communities (Fischer et al 2012, MacGregor-Fors et al 2013 or Notes: AIC, Akaike's information criteria corrected. Averaged estimate, 95% confidence interval (CI), and relative importance (RI) for each parameter are shown and parameters deemed as influential to rodent abundance italicized.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Malo et al (2012) found that an invasive shrub bolstered abundance of wood mice (Apodemus sylvaticus) by reducing predation risk from avian predators. Similar patterns with respect to invasive plants have been observed in the avian literature when entire communities (Fischer et al 2012, MacGregor-Fors et al 2013 or Notes: AIC, Akaike's information criteria corrected. Averaged estimate, 95% confidence interval (CI), and relative importance (RI) for each parameter are shown and parameters deemed as influential to rodent abundance italicized.…”
Section: Discussionsupporting
confidence: 71%
“…, MacGregor‐Fors et al. ) or foraging guilds (French and Zubovic ) are examined. However, with regard to Ord's kangaroo rats in particular, our finding appears to be novel and runs contrary to those of Litt and Steidl (), who found that heteromyid abundance decreased in a linear fashion as cover of a non‐native grass increased.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the changes in cover and forage availability, along with a host of other changes to habitat composition, exotic plants are a large mechanism of disturbance (Knapp 1996, Thompson and Gese 2013, Freeman et al 2014. Support for the intermediate disturbance hypothesis has been observed for several bird communities (Malavasi et al 2009, Fischer et al 2012, MacGregor-Fors et al 2013, but rarely in rodent communities (Malick et al 2012). We feel our observed increase may have been driven by Ord's kangaroo rat, the most abundant species during the study.…”
Section: ]mentioning
confidence: 61%
“…Among the various examples reported in the literature, highlighting the role of tamarisks in the alteration of some habitats and in the composition of flora and fauna, we can mention that of Tamarix ramosissima Ledeb. which has been related to several environmental changes in North America, and it negatively affected avian communities and bird nests (MacGregor-Fors & al. 2013).…”
Section: Notes On Invasivenessmentioning
confidence: 99%